Proximity proteomics reveals UCH-L1 as an essential regulator of NLRP3-mediated IL-1β production in human macrophages and microglia - Liang,Z; Damianou,A; Vendrell,I; Jenkins,E; Lassen,FH; Washer,SJ; Grigoriou,A; Liu,G; Yi,G; Lou,H; Cao,F; Zheng,X; et al. (Cell Reports, 2024)
Activation of the NACHT, LRR, and PYD domains-containing protein 3 (NLRP3) inflammasome complex is an essential innate immune signaling mechanism. To reveal how human NLRP3 inflammasome assembly and activation are controlled, in particular by components of the ubiquitin system, proximity labeling, affinity purification, and RNAi screening approaches were performed. Our study provides an intricate time-resolved molecular map of different phases of NLRP3 inflammasome activation. Also, we show that ubiquitin C-terminal hydrolase 1 (UCH-L1) interacts with the NACHT domain of NLRP3. Downregulation of UCH-L1 decreases pro-interleukin-1β (IL-1β) levels. UCH-L1 chemical inhibition with small molecules interfered with NLRP3 puncta formation and ASC oligomerization, leading to altered IL-1β cleavage and secretion, particularly in microglia cells, which exhibited elevated UCH-L1 expression as compared to monocytes/macrophages. Altogether, we profiled NLRP3 inflammasome activation dynamics and highlight UCH-L1 as an important modulator of NLRP3-mediated IL-1β production, suggesting that a pharmacological inhibitor of UCH-L1 may decrease inflammation-associated pathologies.